A modelling study of OH, NO3 and H2SO4 in 2007–2018 at SMEAR II, Finland: analysis of long-term trends. Issue 6 (1st September 2021) - Chen, Dean; Xavier, Carlton; Clusius, Petri; Nieminen, Tuomo; Roldin, Pontus; Qi, Ximeng; Pichelstorfer, Lukas; Kulmala, Markku; Rantala, Pekka; Aalto, Juho; Sarnela, Nina; Kolari, Pasi; et al.
Abstract : We applied the 1D model SOSAA to simulate the atmospheric concentrations of OH, NO3, and H2 SO4 from 2007 to 2018 at SMEAR II. The results showed that daily OH increased by 2.39% per year and NO3 and H2 SO4 decreased by 3.41% per year and 2.78% per year, respectively. Abstract : Major atmospheric oxidants (OH, O3 and NO3 ) dominate the atmospheric oxidation capacity, while H2 SO4 is considered as a main driver for new particle formation. Although numerous studies have investigated the long-term trend of ozone in Europe, the trends of OH, NO3 and H2 SO4 at specific sites are to a large extent unknown. The one-dimensional model SOSAA has been applied in several studies at the SMEAR II station and has been validated by measurements in several projects. Here, we applied the SOSAA model for the years 2007–2018 to simulate the atmospheric chemical components, especially the atmospheric oxidants OH and NO3, as well as H2 SO4 at SMEAR II. The simulations were evaluated with observations from several shorter and longer campaigns at SMEAR II. Our results show that daily OH increased by 2.39% per year and NO3 decreased by 3.41% per year, with different trends of these oxidants during day and night. On the contrary, daytime sulfuric acid concentrations decreased by 2.78% per year, which correlated with the observed decreasing concentration of newly formed particles in the size range of 3–25 nm with 1.4% per year at SMEAR II during the years 1997–2012. Additionally, we compared our simulated OH, NO3 and H2 SO4 concentrations with proxies, which are commonly applied in case a limited number of parameters are measured and no detailed model simulations are available.